Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1002/bdra.20401
|View full text |Cite
|
Sign up to set email alerts
|

Interpreting changes in the epidemiology of anencephaly and spina bifida following folic acid fortification of the U.S. grain supply in the setting of long‐term trends, Atlanta, Georgia, 1968–2003

Abstract: Our analysis suggests that changes in AN and SB surrounding folic acid fortification (Period 3) could be part of preexisting trends. This must be considered when evaluating prevention efforts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 19 publications
2
31
0
Order By: Relevance
“…Although it has been suggested that declines in the prevalence of spina bifida and anencephaly in the postfortification period may be the continuation of a long-term progressive decline that started long before the mandatory fortification of enriched cereal grain products (CDC, 1992b;Besser et al, 2007), we were unable to evaluate this hypothesis because the surveillance data used for this analysis are only available from 1995-2004. While many of the state-based surveillance programs included in this analysis use active case-finding methods, data for a number of these programs were limited to passively ascertained data, in several instances focusing only on cases identified among liveborn infants (National Birth Defects Prevention Network, 2004).…”
Section: Discussionmentioning
confidence: 94%
“…Although it has been suggested that declines in the prevalence of spina bifida and anencephaly in the postfortification period may be the continuation of a long-term progressive decline that started long before the mandatory fortification of enriched cereal grain products (CDC, 1992b;Besser et al, 2007), we were unable to evaluate this hypothesis because the surveillance data used for this analysis are only available from 1995-2004. While many of the state-based surveillance programs included in this analysis use active case-finding methods, data for a number of these programs were limited to passively ascertained data, in several instances focusing only on cases identified among liveborn infants (National Birth Defects Prevention Network, 2004).…”
Section: Discussionmentioning
confidence: 94%
“…The smallest decrease occurred in the state of California in the USA (15?5 %) (23) . Twenty-one articles reported on the prevalence of spina bifida before and after flour fortification (15,16,19,(21)(22)(23)25,26,28,(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41) . The largest reductions reported were in Costa Rica (61 %) (28) , Canada (55 %) (21) and Chile (55 %) (25) The latter study examined the number of NTD cases between the years 1998 and 2007.…”
Section: Resultsmentioning
confidence: 99%
“…For example, using data from surveillance to evaluate the success of folic acid fortification programs is difficult because of the high frequency of prenatal diagnosis and TOP and the difficulty in separating the effects of the intervention from changes in prenatal diagnosis and TOP over time (Besser et al, 2007); in this situation, alternate strategies such as bio-monitoring might be warranted (Oakley et al, 2008).…”
Section: Discussionmentioning
confidence: 99%